Effect of some air pollutants (sticking minutes and lead) on human health (Journal of the College of Education for Women, 2019)
Air pollution is one of the complex problems plaguing the environment at the present timeas a result of many liberation of gases, vapors and fumes of fuels and chemicals resultingfrom industrial activities . It should be noted that there are some elements of the heavy(Heavy Metals), including toxic in the air, with different concentrations in the air dependingon the nature of the area, for example be in rural areas is lower than in cities or industrialareas as measured parts million (ppm ) or parts per billion (ppb). Some of these importantelements in the physiological processes and enzymatic organisms but become toxic andQatlhand-increase Tercisahaan the permissible limits Bhave nature ,The air contaminantcontaining the lingering minutes, lead and heavy metals have bad effects on human health,causing various diseases. So the goal of this study to know Atrthelot the air in minuteslingering element lead on human health through to identify the causes of serious air pollutionfirst and then the impact of all of the outstanding minutes and lead to human health.